Analisis Genangan Sungai Bailang Akibat Kombinasi Debit Sungai dan Pasang Surut menggunakan Program Mike 21 - Moningka, Frederiko Marchiano Imanuel; Thambas, Arthur Harris; Hendratta, Liany Amelia (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
The coastal area of Manado City, particularly the estuary of the Bailang River in Bunaken District, frequently experiences inundation due to the complex interaction between river discharge and tidal fluctuations. This study aims to analyze the spatial distribution and extent of flooding resulting from the combination of river discharge and tides, as well as to evaluate mitigation strategies based on numerical modeling results. A two-dimensional hydrodynamic model was developed using MIKE 21 Flow Model FM HD, utilizing topographic and bathymetric data from DEMNAS and BATNAS, along with 2023 river discharge and tidal data. Simulations were conducted for existing conditions, minimum discharge with maximum tide, and maximum discharge with maximum tide. The results show that tidal influence significantly contributes to the increase in flood extent and duration, especially when high river discharge coincides with peak tidal conditions. The most affected areas are Kelurahan Molas and Tumumpa, located along the riverbanks and near the fish auction port, with inundation covering up to 4.973 hectares and water depths exceeding 0.5 meters. Recommended mitigation strategies include river normalization and the implementation of a real-time hydrodynamic early warning system. This study supports flood risk management and coastal spatial planning, serving as a technical reference for local government policy-making.